Health education about the dangers of free sex and drugs in adolescents at Tongging village - Ginting, Herli; Margaretha, Lidwina; Simatupang, Grace; Polin, Philip; Rangkuti, Khairunnisa (Talenta Publisher, 2019)
Nowadays drugs have become a scourge for society and the government as something that is very dangerous. The misuse and illicit trafficking of narcotics, psychotropic substances and other dangerous substances (drugs) with various implications and negative impacts is an international problem and threatens the lives of people, nations and countries and can weaken national resilience which at first could hinder the course of development, as well as the rise of free sex . Based on these problems the development or counseling of health education on drug abuse and free sex among adolescent students of Karya Tongging Junior High School in Tongging village needs to be provided so that students can better understand and as a deterrent against negative influences. The method used in the implementation of this activity is the lecture method , discussion and question and answer. Lectures and questions and answers were used to explain the characteristics and motor development of the Tongging Karya Junior High School students. Factors causing juvenile delinquency and the role of overcoming juvenile delinquency, the effect of narcotics use, psychotropic substances of other dangerous substances (drugs), and the effect of free sex among adolescents (sex education for adolescents). It also uses film media to support the smooth information provided.